A novel design strategy of a practical carbon anode material from a single lignin-based surfactant source for sodium-ion batteries. Issue 45 (30th April 2020) - Li, Changhao; Sun, Yi; Wu, Qiujie; Liang, Xin; Chen, Chunhua; Xiang, Hongfa
Abstract : A schematic illustration showing the preparation of HCM from a single sodium lignin sulfonate source and the process of Na storage. Abstract : A novel design strategy for synthesizing hard carbon microspheres (HCMs) from a single source of sodium lignin sulfonate is proposed for a practical anode material of sodium-ion batteries. The HCM has an optimized microstructure, including an enlarged interlayer spacing and few defects, along with a low specific surface area. As an anode material of sodium-ion batteries, HCM is highly promising for practical applications because of its high capacity and reversibility.